Developing and implementing a knowledge management strategy in a muti-cultural engineering design environment - Temple, John (Cranfield University, 2006)
This thesis is about the development and implementation of a Knowledge Management Strategy in a multi-cultural engineering design environment in the automotive industry. It aims to use knowledge management as a vehicle for organisational change by first, understanding the cultural interactions between partners on their models of learning and then to develop and trial a set of tools and frameworks to raise the capability and improve the efficiency of Nissan Technical Centre Europe. The main argument of this thesis is that national culture is so invasive and influential on organisational culture that it can become dysfunctional in a global organisation. The “way we do things around here” is a powerful mechanism by which people value themselves and build their identities. Through an action research approach to the design and implementation of a knowledge management strategy the thesis argues that, rather than try to homogenise cultures, global companies need to maximise the different cultural strengths and create agendas for dialogue. In the longer term this will help build relationships, understanding and empathy and ultimately enhance capability. Organisational cultures cannot be dictated but they can be shaped. Operationally, things may appear to be the same across borders but the cultural mechanisms to facilitate operations are inherently different; this difference needs to be understood and appreciated. Organisational efficiency depends on being able to draw on nationalistic and organisational cultural strengths whilst accepting that these strengths need balancing to ensure they do not become self defeating. The conclusion of the thesis is that knowledge management at Nissan is a process of cultural change, shaped by those in positions of power at any given point in time and dependent on the interaction of structural, organisational, technological and procedural elements which cannot be treated separately and that efficiency, sustainability and the beginnings of a knowledge based learning culture can be realised by organising around knowledge and that knowledge management and organisational learning depend on developing a global mindset which allows for a variety of cultural contexts.